Mikroinvazivni karcinom materničnega vratu - Smrkolj, Špela (Zdravniški vestnik, 2011)
Cervical cancer is the second most common type of cancer among women in the world, and is one of the leading causes of death among cancer deaths in developing countries. The incidence rate of cervical cancer for Slovenia in 2009 was 12.5 per 100,000 females; by frequency it takes the eighth place among female cancers. Microinvasive carcinoma of the cervix is carcinoma with maximum depth of stromal invasion of 5 mm and maximum horizontal spread of 7 mm. The objective of this review is to present the definition of microinvasivecarcinoma of the uterine cervix, to define the diagnostic protocol and treatment of patients with microinvasive carcinoma of the uterinecervix.
Keywords: maternični vrat; rak (medicina)